Development of E-LKPD ecology and biodiversity using PBL-SSI to enhance secondary students' environmental literacy - Melina Siska Ayuwaningsih; Aditya Marianti; Andin Irsadi; Novi Ratna Dewi; Arif Widiyatmoko (JURNAL BIOEDUKATIKA, 2025)
The lack of material in teaching materials related to the environment around students is one of the causes of low environmental literacy. This results in low student knowledge of environmental issues and solutions to these problems. Problem-based learning is an alternative solution for students to practice analyzing problems using a socio-scientific issues approach. The research on the development of E-LKPD Ecology and Biodiversity by integrating the PBL-SSI learning model aims to enhance secondary students' environmental literacy. The type of research conducted is research and development (R&D) with the ADDIE development model, using a pre-experimental design with a group pretest-posttest design. This research was conducted at SMP N 3 Bawang in class VII using a small-scale test with 9 students and a large-scale test with 120 students. The results of this study were declared valid with high score criteria consisting of a material expert validity value of 0.93 and a media expert validity value of 0.94. This research is also very practical with a value of 98.48%, and very effective, with a value of 84.4%. Based on the results of data analysis, it can be seen that the E-LKPD Ecology and Biodiversity can improve students' environmental literacy.